Socialization and Education on the Use of the SAKTI Application for Bawaslu Employees of Pakpak Bharat Regency: Sosialisasi dan Edukasi Penggunaan Aplikasi SAKTI Bagi Pegawai Bawaslu Kabupaten Pakpak Bharat - Elisabet Siregar; G. Oka Warmana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Advances in information technology have driven the transformation of financial management systems in government agencies through the integration of digital platforms such as the Agency-Level Financial Application System (SAKTI). Although this application has the potential to increase transparency and efficiency, its utilization is still not optimal due to limited technical understanding of users. This activity aims to provide structured socialization and education on the use of the SAKTI application for employees at the Pakpak Bharat Regency Bawaslu Secretariat. This program was implemented for two days through interactive sessions, theoretical presentations, and practical simulations. On the first day, participants discussed the application workflow, while the second day focused on practical exercises involving data input and financial reporting. The evaluation results showed a significant increase in participants' understanding and technical skills. These findings indicate that technical guidance and participatory methods are effective in improving user competence in digital financial management. This initiative contributes to encouraging accountable and transparent governance through strengthening internal financial supervision supported by increasing human resource capacity.